Взаимодействие железоуглеродных нанотрубок с модельным раствором желудочного сока - Бошицкая, Н.В.; Иващенко, Е.А.; Прилуцкий, Э.В.; Прилуцкий, О.В.; Уварова, И.В. ("Доповіді НАН України", 2007)
The stability of iron-carbon nanotubes to the influence of a model solution of gastric juice is studied. 0.1 n hydrochloric acid is taken as a model solution, and the interaction time was varied from 30 min to 8 days. It is established that the intensive separation of iron from iron-carbon nanotubes takes place during two hours, then the process is practically stopped. It is supposed that two parallel processes take place: the separation of iron from nanotrubes and its sorption on the carbon structures of nanotubes. It is established that iron-carbon nanotubes save sufficient magnetic properties in spite of the active separation of iron from them.